Neprilysin, the kidney brush border neutral proteinase: a possible potential target for ischemic renal injury. (12th February 2020) - Sankhe, Runali; Kinra, Manas; Mudgal, Jayesh; Arora, Devinder; Nampoothiri, Madhavan
Abstract: Neprilysin (NEP) is an endogenously induced peptidase for modulating production and degradation of various peptides in humans. It is most abundantly present in kidney and regulates the intrinsic renal homeostatic mechanism. Recently, drugs inhibiting NEP have been approved for the use in heart failure. In the context of increased prevalence of ischemia associated renal failure, NEP could be an attractive target for treating kidney failure. In the kidney, targeting NEP may possess potential benefits as well as adverse consequences. The unfavorable outcomes of NEP are mainly attributed to the degradation of the natriuretic peptides (NPs). NPs are involved in the inhibition of the renin–angiotensin–aldosterone system (RAAS) and activation of the sympathetic system contributing to the tubular and glomerular injury. In contrary, NEP exerts the beneficial effect by converting angiotensin-1 (Ang I) to angiotensin-(1–7) (Ang-(1–7)), thus activating MAS-related G-protein coupled receptor. MAS receptor antagonizes angiotensin type I receptor (AT-1R), reduces reactive oxygen species (ROS) and inflammation, thus ameliorating renal injury. However, the association of NEP with complex cascades of renal ischemia remains vague. Therefore, there is a need to evaluate the putative mechanism of NEP and its overlap with other signaling cascades in conditions of renal ischemia.